Square root of-100x^4y^13

Answers

Answer 1
Answer:

Answer:

10x^2y^6√y

Step-by-step explanation:

1. First, let's factor out any perfect squares from the expression under the square root. In this case, we can factor out 100, which is a perfect square:

√(100 * x^4 * y^13)

2. Taking the square root of 100 gives us 10:

10 * √(x^4 * y^13)

3. Now, let's simplify the expression under the square root. Remember that the square root of a product is equal to the product of the square roots:

10 * √(x^4) * √(y^13)

4. The square root of x^4 is x^2:

10 * x^2 * √(y^13)

5. Finally, let's simplify the square root of y^13. Since 13 is an odd number, we can write it as the product of a perfect square and an additional factor:

10 * x^2 * √(y^12 * y)

6. The square root of y^12 is y^6:

10 * x^2 * y^6 * √y

Therefore, the simplified expression for the square root of -100x^4y^13 is:

10x^2y^6√y


Related Questions

A cone has a base radius of 5cm and a vertical height of 12cm. Calculate the total surface area of the cone.
The radii of Earth and Pluto are 6,371 kilometers and 1,161 kilometers, respectively. Approximately how many spheres the size of Pluto does it take to have the same volume as Earth?
The school you want to go to has an acceptance rate of 12%. That means that 12% of the students who apply to the school get in. The school took in 2,400 students last year. How many students applied?
Mara carried water bottles to the field to share with her team at halftime. The water bottles weighed a total of 60x2 + 48x + 24 ounces. Which factorization could represent the number of water bottles and weight of each water bottle? 6(10x^2 + 8x + 2) 12(5x^2 + 4x + 2) 6x(10x^2 + 8x + 2) 12x(5x^2 + 4x + 2)
Solve for x in the equation x squared + 2 x + 1 = 17.x = negative 1 plus-or-minus StartRoot 15 EndRootx = negative 1 plus-or-minus StartRoot 17 EndRootx = negative 2 plus-or-minus 2 StartRoot 5 EndRootx = negative 1 plus-or-minus StartRoot 13 EndRoot

The rate traveled from Amarillo to Austin by a bus averages 65 miles per hour. The bus arrived in Austin after eight hours of travel. An automobile averages 80 miles per hour. Using the inverse variation relationship, show what the time would be for the automobile to complete the trip.

Answers

If it takes 8 hours for a bus with an average velocity of 65mph to travel from Amarillo to Austin then,
d = 65 (8) = 520 miles

The distance from Amarillo to Austin (or vice versa) is 520 miles.

If the function to get the distance traveled by the automobile is given by:
d(x) = 80 t
Then, the inverse variation relationship would be
d-1(x) = t = d / 80
Since d = 520
t = 520 / 80
t = 6.5 hours

It takes 6.5 hours for the automobile to complete the trip

What would my final balance be if i put $650 in the bank for 60 months with an interest rate of 6%?

Answers

Your final balance would be $2,340.

I = Prt
Percent (6%) x rate (650) x time (60 months) = 2,340

6% = 0.06

0.06 x 60 x 650 = 2,340


Final answer:

You would end up with approximately $871.89 in your bank account after investing $650 for 60 months at an annual interest rate of 6%, if the bank compounds the interest yearly.

Explanation:

In this case, we are calculating the compound interest over a certain period. The formula for compound interest is:

P = C * (1 + r/n)^(nt)

  1. C is the initial deposit (the principal). In your case, this is $650.
  2. The interest rate (r) is 6%. To use this in the formula, we need to convert it to decimal form by dividing by 100, so r = 0.06.
  3. n is the number of times that interest is compounded per unit t. Since it's not stated in the question, we'll assume it is once per year.
  4. t is the time the money is invested for in years. Converting your 60 months to years gives t = 60/12 = 5 years.

Substitute the values into the formula:

P = $650 * (1 + 0.06/1)^(1*5)

Applying mathematics, we get an approximate final balance of $871.89

Learn more about Compound Interest here:

brainly.com/question/34614903

#SPJ3

Which mathematical term cannot be precisely defined?

Answers

The mathematical term that cannot be precisely defined is point.....Here you go and this is the correct answer

The quadratic equation (3k-2)x^2 +12x+3(k+1) =0 has equal roots. Find the two possible values of k.

Answers

x_1=x_2 \Rightarrow \Delta=0\n\Delta=12^2-4\cdot(3k-2)\cdot3(k+1)\n\Delta=144-(36k-24)(k+1)\n\Delta=144-36k^2-36k+24k+24\n\Delta=-36k^2-12k+168\n-36k^2-12k+168=0\n-3k^2-k+14=0\n-3k^2+6k-7k+14=0\n-3k(k-2)-7(k-2)=0\n-(3k+7)(k-2)=0\nk=-(7)/(3) \vee k=2

Create a graph of the combined function h(x) = f(x)/ g(x) in which f(x) = x - 6 and g(x) = x + 6.On your graph, show the graphs of f(x) and g(x) also.

Answers

Answer:

In the picture attached the graph of h(x) = f(x)/ g(x) = (x - 6)/(x + 6) is shown. Notice that there is no h(x) for x = -6. The graph was made with a computer software

f(x) = x - 6 and g(x) = x + 6 are also included. These two functions are continuous for all real numbers, despite that h(x) is not continuous in x = -6

The Graphs of tan, cot, csc, sec. ... The graphs of y = tan(x) and y = cot(x) have the same x-values for y-values of 1 and ...

Kendra is buying bottled water for a class trip.She has 16 bottles left over from the last trip.She buy bottles by case to get a good price.Each case holds 24 bottles.How many cases will she to have to buy if she wants to have a total of 160 bottles of water??.

Answers

She will have to get 6 cases of water.